Comments to AAP Cádiz N° 242/2018 of 13 November: execution in Spain of a judgment delivered in Guadalupe. Seizure of ship - Romero Matute, Yeray (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
In this dissertation, the aim is, in line with Order No. 242/2018 of the Provincial Court of Cadiz, to analyze the behavior and resolutions issued by the Commercial Court of the same city. As well as establish the order of precedence of International Treaties and Conventions and the internal regulations of each Member State. All this, related to the existence of a maritime credit between two companies, leading to the preventive seizure of a ship moored in the port of the bay of Algeciras, owned by one of the parties. Also, the rules of Private International Law will be studied, with the aim of elucidating which court is competent to know, recognize and enforce such seizure.
Keywords: ship; preventive seizure; competent court; recognition and enforcement